Soeharto's new order and its legacy : essays in honour of Harold Crouch - Aspinall, Edward; Fealy, Greg, 1957-; Crouch, Harold A., 1940- (Asian studies series monograph ;, 2010)
"Indonesia's President Soeharto led one of the most durable and effective authoritarian regimes of the second half of the twentieth century. Yet his rule ended in ignominy, and much of the turbulence and corruption of the subsequent years was blamed on his legacy. More than a decade after Soeharto's resignation, Indonesia is a consolidating democracy and the time has come to reconsider the place of his regime in modern Indonesian history, and its lasting impact. This book begins this task by bringing together a collection of leading experts on Indonesia to examine Soeharto and his legacy from diverse perspectives. In presenting their analyses, these authors pay tribute to Harold Crouch, an Australian political scientist who remains one of the greatest chroniclers of the Soeharto regime and its aftermath."--Publisher's description